Technology Adoption Among Town Planners in Malaysia - Abdullah, Jamalunlaili; Marzukhi, Marlyana Azyyati; Danial, Muhammad Hakim; Ghani, Mohd Khairolden; Kokchang, Phimsupha (International Journal of Sustainable Construction Engineering and Technology, 2023)
The integration of technology in the planning practices of the Malaysian construction industry has significantly transformed how planners approach the development process. The objective of this research is to examine the extent to which technology has been adopted in planning practices in Malaysia. To accomplish this, a mixed methods approach was used, which involved distributing an electronic survey form to the members of the Malaysian Institute of Planners (MIP). The study has revealed three important findings. Firstly, for software adoption rates, the majority of respondents used basic storage, communication, CAD, graphic design, and GIS software with varying skill levels. On the other hand, hardware adoption rates were lower, likely due to financial constraints, and most respondents had average skills in operating GPS, drones, remote sensing, cloud computing, and 3D printing hardware. Secondly, the annual budget for most organisations was below RM30,000, with software subscriptions accounting for the largest budget allocation. Lastly, financial resources, a lack of skilled workers, and network constraints were identified as the biggest challenges faced by planning agencies in adopting technology. The research suggests that providing grants for technology adoption for small firms and local authorities, standardisation of systems, and flexible data sharing can increase productivity in planning activities across agencies. In summary, planners must adapt to technology due to the increasing demand for new development. Effective data management is required for decision-making. Malaysia’s government and planners are willing to adopt technology for increased productivity, and recent developments such as I-Plan and OSC 3.0 Plus Online demonstrate a commitment to data-driven decision-making. There is still much to learn and improve for planners in the public and private sectors to contribute to the success of the construction industry in Malaysia.